Impact of structured pre-natal counselling on early initiation of breast feeding and adherence to exclusive breast feeding: a comparative interventional study - Koli, Hiral B.; Nair, Mudra Gopidas; Shah, Maitri C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The importance of early initiation of breast feeding (EIBF) and exclusive breastfeeding (EBF) is widely recognized, but the optimum rates have not been attained due to several factors. One of the important factors is the lack of adequate knowledge of women regarding breastfeeding. Methods: This comparative intervention study was conducted in the obstetric OPD and postnatal wards of tertiary care hospital of central Gujarat. This study included antenatal women between gestational age of 28 to 38 weeks who are visiting obstetric OPD at our institute and wanted to deliver at the same as cases (356 participants) and postpartum women who were delivered at this institute who have not taken antenatal care and counselling at this institute as control. Results: This study concluded that prenatal counselling regarding breast feeding had significant impact on the improvement of knowledge of women regarding EIBF and Exclusive breast feeding. Rate of EIBF and EBF was 91.85% and 86.52% in case group which was significantly higher compared to the control group. Conclusions: Prenatal structured counselling helps to raise the rate of EIBF and EBF.